GaAs solar cell on Si substrate with good ohmic GaAs/Si interface by direct wafer bonding - Kim, SangHyeon; Geum, Dae-Myeong; Park, Min-Su; Kim, Chang Zoo; Choi, Won Jun (ELSEVIER SCIENCE BV, 2015)
In this work, we developed wafer bonding techniques to bond GaAs and Si wafers. Wafer bonding was carried out at room temperature without high temperature annealing processes. The bonded interface showed a low interface resistance of 8.8 x 10(-3) Omega cm(2). We also exploited the new bonding techniques to fabricate a GaAs solar cell on a Si substrate. The solar cell showed a high energy conversion efficiency (13.25%) even without an anti reflection coating. The performance of the fabricated GaAs/Si solar cell was comparable to that of a homogeneous GaAs solar cell grown on a GaAs substrate. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: EFFICIENCY; DISLOCATIONS; CONVERSION